Chloride ion penetration into fly ash modified concrete during wetting–drying cycles - Simčič, Tina; Pejovnik, Stane; De Schutter, Geert; Bosiljkov, Violeta Bokan (Construction & building materials, 2015)
•Chloride penetration in fly ash concrete under wetting–drying cycles was studied.•Detailed chloride profiles were recorded, including total and free Cl− content.•Higher percentage of ink-bottle porosity means higher chloride resistance.•Thicker cover depths are required for fly ash modified concrete over time. The subject of this paper is the extent to which, during wetting–drying cycles, chloride ions penetrate into fly ash modified concrete. Detailed chloride profiles were recorded which show how the total and water-soluble chloride contents vary with the depth of penetration of these ions into the concrete. In order to study the effect of exposure time, fly ash content, and fly ash composition on such penetration, two different types of fly ash were used as a partial replacement of Portland cement, their proportions amounting to 0%, 20% and 50% by weight of the binder. The results of the investigation showed that the chloride penetration depths were smaller in the case of the fly ash modified concretes than in the case of the unmodified concrete (i.e. concrete which did not contain fly ash), so that thinner layers of concrete cover could in this case be used to protect the steel reinforcement from the effects of corrosion. This indicates the potential beneficial effect of the use of fly ash on the service life of reinforced concrete structures. It is not just the porosity of the fly ash which plays a key role in the case of chloride penetration into concrete, but also the composition of the fly ash, and especially its calcium content.